(untitled) (Ocean and Coastal Research, 2024)
The presence and potential adverse effects of emerging contaminants, such as UV filters and synthetic muskfragrances, in aquatic ecosystems has generated increasing concern. However, information about the sublethaleffects and ecological risks of these substances to non-target organisms remains scarce. A systematic reviewof oxidative biomarkers was performed to better understand the mechanisms of these contaminants in bivalves.Bivalves were chosen as the focus of this study because they can provide integrated information related tocontamination by ecotoxicologically relevant substances over time. Bibliographic database searches resultedin 10 articles published from 2019 to 2023. The biomarkers superoxide dismutase, catalase, glutathioneperoxidase, and glutathione reductase showed promising responses (increase or decrease) in the presence ofUV filters (oxybenzone, enzacamene, and octocrylene) and fragrances (galaxolide and tonalide). GlutathioneS-transferase showed the most significant increase in response to these compounds, making it the mostpromising biomarker. Our results indicate a limited number of studies on the toxicity of personal care products,highlighting the need for further research in this area.